'He's got his father's bias': Parental influence on weight bias in young children. (15th December 2015) - Spiel, Emma C.; Rodgers, Rachel F.; Paxton, Susan J.; Wertheim, Eleanor H.; Damiano, Stephanie R.; Gregg, Karen J.; McLean, Siân A.
Abstract : Our aim was to explore the role of parents in the transmission of stereotypical body size attitudes and awareness of weight loss strategies to preschool children. Participants were 279 3‐year‐old children and their parents, who provided data at baseline and 1 year later. Parents completed self‐report body size attitude and dieting measures. Child weight bias and awareness of weight loss strategies were assessed through interview. Over time, negative associations with large bodies and awareness of weight loss strategies increased. Fathers' attitudes prospectively predicted boys' weight bias and awareness of weight loss strategies. Among girls, parental attitudes were less predictive. Findings confirm the importance of fathers in the development of boys' body attitudes and inform prevention programmes.